Hedge, Diversifier and Safe Haven Properties of Precious Metals against UK Stocks During COVID-19 Pandemic - Ikram Ul Haq; Farzan Aslam; Fakhra Aslam, (Dialogue Social Science Review (DSSR), 2024)
This research study examines the hedging, safe haven, also diversification properties of precious metals, specifically silver, gold, and platinum, in relation to the UK stock market. To evaluate the hedging and safe haven qualities of precious metals, this research paper uses a multivariate vine copula-based GARCH model. To investigate the diversification ability of precious metals, a Bivariate Value at Risk-based copula (BiVaR) method are utilized. According to our empirical findings, which are in line with earlier research, gold, a precious metal, offers the UK the best safe haven property during the COVID-19 pandemic. Gold may thus be used to counteract equities market losses during turbulent times. Nevertheless, since silver is supplementary lightly traded, commanding it most illiquid and volatile, it is not seen as a safe haven asset for the other UK stock markets. Regarding platinum, it is a poor hedge and a gold mine for the UK stock market. Additionally, consistent with previous research, our analysis indicates that gold maintains a powerful hedging ability in established stock markets. The findings suggest that platinum and silver might function as weak hedging assets. Lastly, all precious metals show diversification advantages for investors in UK stock markets, according to the BiVaR analysis's findings. Overall, our findings may be quite advantageous to investors.